Monitoring Sistem Pengolahan Lahan TPU Di Kantor Pemakaman Daerah Kabupaten Tangerang - Dina Fitria Murad; Hendro Hendro; Imanuel Revelino Murmanto (Universitas Multimedia Nusantara, 2016)
Submission of the necessary permits public land burial place in the office area of Tangerang Regency funeral submitted by housing developers located in Tangerang district in order to meet the requirements of the Licensing process IMB. Now all land data submission submitted in writing through several procedures with the data fields that tend to repeat themselves. At the Office of Cemeteries Regional delivery of new land submitted by the developer to Tangerang Regency is still to record any data into a ledger and using Microsoft Office Excel, the data is recorded repeatedly and it resulted in the data search Proof of Ownership of Land TPU submitted by the developer housing to local government Tangerang any time the data is needed to be delayed. Some of the observations made to the current system in the data collection process of handing over land where the public cemetery (TPU) result of research that the problems being faced by the Office of the particularly within the system of delivery of TPU to Tangerang Regency include the length of time the process because of the many documents and procedures in each section must be followed to check files and keabshan data submitted. Keywords : land, developers, public cemetery